Effect of age on thickness of adult patellar articular cartilage. - Meachim, G (1977)
The thickness of left patellar articular cartilages after formalin fixation was studied in a series of autopsies on 82 subjects aged 25-96 years. For each specimen the minimal uncalcified cartilage thickness in a transverse patellar slab was determined separately for a 'lateral' segment and a 'central and medial' segment. In the women the cartilage from subjects more than 50 years old showed progressive thinning with increasing age. This was due to lesions causing disintegration of the tissue and not to matrix shrinkage. It had a strong potential to progress to full-thickness cartilage loss in the older women, and to give an appearance indistinguishable from osteoarthrosis as seen in surgical excision specimens. This progression towards patellofemoral osteoarthrosis in the elderly affects the female population generally, and not just a special subgroup; however, the incidence of clinical symptoms from this cause is not known. In men progressive thinning with age of patellar cartilage in subjects more than 50 years old was less severe, especially so in the case of the 'lateral' segment; a site of full-thickness uncalcified cartilage loss on the left patella at autopsy was seen only occasionally in the older men.